Preparation, characterization and application of polymeric ultra-permeable biodegradable ferromagnetic nanocomposite adsorbent for removal of Cr(VI) from synthetic wastewater: kinetics, isotherms and thermodynamics - Evans Suter; Hilary Rutto; Robert Makomere; Musamba Banza; Tumisang Seodigeng; Sammy Kiambi; Wesley Omwoyo (Frontiers in Environmental Chemistry)
Hexavalent chromium (Cr(VI)) contamination in drinking water due to industrial activities is a growing worldwide concern. Cr(VI) concentrations exceeding a few parts per billion (ppb) can cause serious health problems such as asthma, blood cancer, kidney-related diseases, liver and spleen damage, as well as neurological system, immunological deficiencies, and reproductive issues. This study, thus, explored the feasibility of employing a novel polymeric ferromagnetic nanocomposite adsorbent made of low-cost, biodegradable, and ultra-permeable materials from pulp and paper sludge for adsorptive removal of hexavalent chromium (Cr6+) from synthetic wastewater. Vibrating-sample magnetometer (VSM), X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmet-Teller surface area (BET), and Fourier transform infrared (FTIR) were used to analyze the produced nanocomposite adsorbent. The Fourier transform infrared results confirmed the presence of adsorptive peaks attributed to −OH, −NH2, and FeO. Scanning electron microscopy micrographs revealed a porous adsorbent surface. XRD revealed the existence of the crystalline spinel-structured magnetite (Fe3O4) phase of iron oxide, while the saturation magnetization was established to be 26.90 emu/g. The Brunauer–Emmett–Teller analysis confirmed a slight decrease in the surface area of the nanocomposite adsorbent to 6.693 m2.g−1, compared to Fe3O4 (7.591 m2.g−1). The optimum conditions for Cr6+ removal were pH 2.0, 1.0 g/L adsorbent dose, room temperature (25°C), 120 min contact time, and 20 mg/L pollutant concentration. During removal, the Cr(VI) was adsorbed by electrostatic attraction and/or reduced to trivalent chromium Cr(III). At low starting Cr(VI) concentrations, chemisorption dominated the removal process, but as concentrations increased, physisorption became more significant. The prepared nanocomposite adsorbent presented exceptional removal efficiency of up to 92.23%, indicating that it may be useful for the adsorption of metal ions from industrial and household wastewater.